(untitled) (Third Sector Social Economic Review, 2024)
Environmental policies are important for a sustainable environment. Uncontrolled use of pesticides, fertilizers, and pesticides increasing efficiency, causes serious environmental damage. Environmental regulations may impose various restrictions on the use of these products. The use of these elements above the recommended level may lead to an increase in efficiency. Reducing the use of these elements through environmental regulations may encourage full capacity use and ensure the same production rate without causing financial loss. The stringency of environmental regulations implemented by countries may vary. This difference may lead to different results on the impact of environmental policies on agricultural exports. A panel data application was made with data from 19 OECD countries and the years 2001-2019 to examine the impact of environmental policies on agricultural exports. In the Study, the fixed effects model was determined as the appropriate model. The explanatory power of the model was obtained as 46%. According to the study results, while a significant and negative effect was observed on agricultural exports with the environmental performance index, agricultural labor force, and total factor productivity a significant and positive relationship was obtained with the agricultural producer index and real exchange rate. However, no significant effect was found between the use of growth and agricultural pesticide agricultural exports.